Snakes, Sacrifice, and Sacrality in South Asian Religion - Jones, Gabriel (Université d'Ottawa | University of Ottawa, 2010)
Ritual sacrifice associated with snake veneration is not uniformly expressed. The snake figures prominently in the art and narrative of contemporary Saivism, Vaisnavism, Jainism, and Buddhism in addition to the myriad of popular devotional practices of rural village and peripatetic peoples of India. Drawing on the evidence within the many traditions that have accommodated or rejected the snake as a subject of veneration, this article theorizes its associated sacrifice(s) as a tripartite phenomenon reflecting divergent cultural valuation of the snake across the Indian sub-continent.